The Climate Change Impact on Coral in Weh Island and Aceh Island Indonesia - A. Besse Rimba; Fusanori Miura; Joseph Maina; Abd. Rahman As-syakur; Stuart Campbell (International Journal of Environment and Geosciences, 2019)
Climate change is a global phenomenon that affects all aspects of life. Climate change also affects marine life such as coral reefs. This study aims to determine the effect of climate stress on coral in Weh Island and Aceh Island-indonesia. This study combined ground check time series data with time series data of satellite oceans, data is grouped into two categories. They are biodiversity data and climate stress data. The biodiversity data obtained fish data and coral data from in-situ data since 2005 to 2011 and climate data stress data obtained from compilation of satellite ocean data since 1983 to 2011. Biodiversity data includes number species of fish and the genus of coral biodiversity and coral community susceptibility. Climate stress is grouped into three categories. They are radiation, stress reinforcing and reducing stress. Radiation stress factors consists temperature, UV light and doldrums. Stress-reinforcing factors consists sedimentation and eutrophication. Then stress-reducing factors consists temperature variability and tidal amplitude. Base on the research result shows that climate stress has impact on coral condition. Environmental pressure gives significant effect on biodiversity. The climate-change affects indirect impact on the fish and coral reef. Climate change influences the ocean condition. Some of the biodiversity cannot resist due to the ocean condition changes drastically.